ERICA: prevalence of asthma in Brazilian adolescents - Fábio Chigres Kuschnir; Ricardo Queiroz Gurgel; Dirceu Solé; Eduardo Costa; Mara Morelo Rocha Felix; Cecília Lacroix de Oliveira; Maurício Teixeira Leite de Vasconcellos; Maria Cristina Caetano Kuschnir (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To describe the prevalence of asthma and physician-diagnosed asthma in Brazilian adolescents. METHODS Cross-sectional, national, school-based study with adolescents from 12 to 17 years old, participants in the Study of Cardiovascular Risks in Adolescents (ERICA). The study stratified the sample by region and grouped according to schools and classes with representativeness to the set of cities with more than 100,000 inhabitants of the Country, macro-regions, capitals, and Federal District. A questionnaire collected data through a self-filled in method. We calculated the prevalences and their confidence intervals of 95% (95%CI) according to sex, age group, type of school and skin color. RESULTS Between 2013 and 2014, 74,589 adolescents were evaluated, 55.3% of the female sex. The total prevalence of active asthma was of 13.1% (95%CI 12.1-13.9), being higher in girls (14.8%; 95%CI 13.7-16.0) when compared to boys (11.2%; 95%CI 10.3-12.2) in all geographical strata examined. It was also higher between students of private schools (15.9%; 95%CI 14.2-17.7) when compared to public ones (12.4%; 95%CI 11.4-13.4). It was higher in the Southeast region (14.5%; 95%CI 12.9-16.1), and in the city of Sao Paulo (16.7%; 95%CI 14.7-18.7). The lowest prevalence was observed in North region (9.7%; 95%CI 9.7-10.5), and in Teresina (6.3%; 95%CI 4.9-7.7). The prevalence of physician-diagnosed asthma was of 8.7% (95%CI 8.2-9.1); higher in the North region (13.5%; 95%CI 12.7-14.2), and in Porto Alegre (19.8%; 95%CI 17.5-22.3). It was lower in the Midwest (6.9%; 95%CI 6.0-7.8), and in Cuiaba (4.8%; 95%CI 3.8-5.9). We found no significant difference in the expression of this rate between the sexes, as well as in other variables evaluated by the study. CONCLUSIONS The prevalence of asthma in Brazilian adolescents is high. Rates of active asthma and physician-diagnosed asthma vary widely in different regions and capitals evaluated by the ERICA. These results may assist in the preparation of preventive programs and policies on health and a better understanding of the factors associated with asthma in this age group.